Analisis Yuridis Penugasan PT Jaminan Kredit Indonesia (Jamkrindo) dalam Rangka Penjaminan Kredit Usaha Rakyat (KUR) oleh Badan Usaha Milik Negara Berdasarkan Undang-Undang Nomor 19 Tahun 2003 tentang Badan Usaha Milik Negara Jo. Undang-Undang Nomor 1 Tahun 2025 tentang Perubahan Ketiga atas Undang-Undang Nomor 19 Tahun 2003 tentang Badan Usaha Milik Negara - Raden Sihar Martogi Sinambela; Appe Hutauruk; Hotman Sinambela; Mardiman Sane; Fendi Maruba Parlindungan Hutahaean (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research juridically analyzes the assignment of PT Jaminan Kredit Indonesia (Jamkrindo) in the People's Business Credit (KUR) guarantee scheme based on Law Number 19 of 2003 concerning State-Owned Enterprises, as last amended by Law Number 1 of 2025. Government assignments to SOEs often create an intersection between corporate principles (business judgment rule) and public service obligations. The research method used is normative legal research with a statutory approach. The results show that the assignment of PT Jamkrindo in KUR guarantees is an embodiment of the SOE's function as a constitutionally valid development agent, but requires regulatory harmonization to ensure legal certainty in guarantee risk management. Furthermore, the synchronization of rules regarding capital changes and assignment mechanisms in the latest SOE Law provides a stronger legal basis for PT Jamkrindo in supporting the sustainability of the MSME sector through inclusive financing. The conclusion of this research emphasizes the importance of legal protection for SOE directors in carrying out government assignments to remain accountable and not violate good corporate governance principles.